RESKILLING AND UPSKILLING FOR CIRCULARITY: TALENT MANAGEMENT STRATEGIES TO UNLOCK SMART CIRCULAR ECONOMY OPPORTUNITIES IN THE DIGITAL AGE - Napitupulu, Priskilla E.E.; Dananjaya, Yanuar (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
In the era of digitalization, reskilling and upskilling are pivotal in facilitating the realization of circular economy prospects through the amalgamation of digital technologies and circular economy principles. The integration of Industry 4.0 technologies has the potential to facilitate the execution of circular economy methodologies, particularly for small and medium enterprises, by utilizing digital instruments to bolster the circular transformation. Research indicates how digital technologies, such as artificial intelligence, big data analytics, and the Internet of Things, can enhance circular design principles, resulting in decreased wastage and enhanced material recycling rates in sectors like construction. Moreover, a comprehensive examination of existing literature underscores the significance of deploying diverse digital technologies throughout the product lifecycle to effectively implement circular economy tactics, advancing goals like resource optimization, prolonged product durability, and loop closure. Hence, talent management approaches that concentrate on enhancing the digital and circular economy proficiencies of employees are imperative for fully capitalizing on the potential of the intelligent circular economy model and fostering sustainable innovation and advancement in enterprises. Study literature review, Firstly, this study was focused on the whole articles that had been published from 2016 to 2024; all of which were in published semanticscholar.org. Secondly, this study was devoted to investigating a number of articles that focused primarily on human resources in the smart circular economy in the digital age. Thirdly, various parameters were used as foundations for content analysis. To enhance knowledge on human resources in smart circular economy paradigm, researchers and practitioners are advised to: (i) Skills and Competencies, (ii) Learning and Development (iii) Learning and Development (iv) Change Management